Why do people save in cash? Distrust, memories of banking crises, weak institutions and dollarization - Stix, Helmut (Journal of Banking & Finance, 2013)
The paper analyzes why households hold sizeable shares of their assets in cash at home rather than at banks – a phenomenon that is widespread in many economies but for which information is scarce. Using survey data from ten Central, Eastern and Southeastern European countries, I document the relevance of this behavior and show that cash preferences cannot be fully explained by whether people are banked or unbanked. The analysis reveals that a lack of trust in banks, memories of past banking crises and weak tax enforcement are important factors. Moreover, cash preferences are stronger in dollarized economies where a “safe” foreign currency serves as a store of value.